Impact of caval vein implantation on severity of tricuspid regurgitation, renal and hepatic function in patients with severe secondary tricuspid regurgitation. (25th November 2020) - Mattig, I; Hewing, B; Knebel, F; Stangl, V; Laule, M; Stangl, K; Dreger, H
Abstract: Background: Severe tricuspid regurgitation (TR) is an important determinant for functional capacity and survival. It frequently occurs in patients with advanced heart failure resulting in progressive venous congestion with cardiorenal and cardiohepatic syndrome. The prospective, randomized TRICAVAL study reported the effect of inferior caval vein implantation of an Edwards Sapien XT valve (CAVI) in comparison to optimal medical therapy (OMT) in patients with severe TR. The study did not detect a superior functional outcome after CAVI, but a significant improvement in quality of life. Due to safety concerns, the study was stopped prematurely after 4 periprocedural complications. Purpose: We hypothesised that CAVI reduces reflux into the inferior vena cava and leads to an increase in systolic right atrial pressure, which may result in an improvement of TR severity. The present subanalysis of the TRICAVAL study evaluates the impact of inferior caval vein implantation on TR severity, right heart parameters and renal and hepatic function. Methods: Twenty-eight patients with severe TR were randomized in either CAVI group (n=14) with caval vein implantation of an Edwards Sapien XT valve or OMT group (n=14). Medical history, clinical examination, laboratory testing and echocardiographic measurements were analysed in patients with completed FUP (OMT [n = 10], CAVI [n = 8]). Follow-up examinations were performed at baseline and three months after enrolment. Results: After three months, the CAVI group exhibited a significant reduction of systolic hepatic vein reflux volume (5.0 [1.3–11.0] ml vs. 14.0 [10.3–18.0] ml, p<0.05) and hepatic vein diameter (10.8 [10.0–12.0] mm vs. 14.0 [11.5–15.0] mm, p<0.05) in comparison to OMT. Compared to baseline, CAVI improved body weight (80.7 [69.0–87.7] kg versus 75.5 [63.8–84.6] kg, p<0.05) and abdominal circumference (101.5±13.8 cm versus 96.3±15.4 cm, p≤0.01) paralleled by a trend to lower doses of diuretics. However, over the FUP period, there were no significant changes regarding TR severity, right heart function and morphology as well as renal and hepatic function within both groups, nor in the comparison between CAVI and OMT. Conclusion: As a proof of our concept, CAVI resulted in a decrease in systolic hepatic vein reflux, hepatic vein diameter and clinical signs of venous congestion. However, TR severity, right heart function and morphology as well as renal and hepatic function remained stable. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Edwards Lifesciences, Incorporated (Irvine, CA)